Physicochemical Properties Of Starch From Sago (Metroxylon Sagu) Palm Grown In Mineral Soil At Different Growth Stages - Zain, Noorul Wahidah Mat (2011)
Malaysia is currently the largest world exporter of starch from sago (Metroxylon sagu) palm i.e. 47,000 metric ton/year where 96% from the starch was produced in Sarawak. The major problem faces by the industry or food manufacturer is the variation in quality of sago starch from batch to batch. The existing data are not sufficient to cater the increasing demand for high quality sago starch from the industry. An understanding of basic properties is required to effectively utilize the starch which data is still lacking for sago palm grown in mineral soil.